PERANCANGAN APLIKASI E-CATERING PADA USAHA RABILA CATERING BERBASIS WEB MENGGUNAKAN NOTIFIKASI WHATSAPP GATEWAY - saing, ferdiansyah; Alam, Syahirun; Ika, Nur (Fakultas Teknik Universitas Muhammadiyah Parepare, 2021)
Rabila Catering is one of the caterers in Pinrang City as a provider of food and services for an event or party. Currently, the transaction process that occurs between the catering owner and his customers is still conventional. In addition, the freedom of customers in choosing the menu is still minimal and new customers know the existence of the Rabila Catering place, only limited to consumers in Pinrang City. The result of this research is the Design of an E-Catering Application for a Web-Based Rabila Catering Business Using Whatsapp Gateway Notifications. From applications that have been tested the system created can optimize the use of the previous system where promotions and orders can be web-based and whatsapp gateways, information whether it's menus, packages, promos and orders can be obtained from accessing the website or requesting information via whatsapp, in this way buyers can directly order without having to come to the catering location, this certainly saves costs.